Role of Neurosurgery in Spontaneous Intracranial Hypotension: Initial Experience with Epidural Blood Patch in Nepal (Nepal Journal of Neuroscience, 2026)
Introduction: Spontaneous intracranial hypotension (SIH) is an underrecognized cause of secondary headache resulting from spinal cerebrospinal fluid leakage. It typically presents with orthostatic headache and characteristic imaging findings. Herein, we report two case of SIH treated with epidural blood patch in Nepal.Case Presentation:Case 1: A 55-year-old female presented with orthostatic headache, neck stiffness, and nausea. MRI brain showed features of Spontaneous intracranial hypotension (Bern score 7), and spine MRI demonstrated positive spinal longitudinal epidural collection. She underwent fluoroscopy-guided epidural blood patch (18–20 mL), resulting in immediate symptom relief and complete improvement at 3 months.Case 2: A 45-year-old male presented with a 10-day history of orthostatic headache and cognitive clouding. MRI findings were consistent with Spontaneous intracranial hypotension (Bern score 9) with spinal longitudinal epidural collection positivity on spine imaging. Following fluoroscopy-guided epidural blood patch, he showed rapid clinical improvement with no symptomatic recurrence at 3-month follow-up.Conclusion:To our knowledge, these cases represent first documented case of Spontaneous intracranial hypotension treated with epidural blood patch in Nepal. This report highlights not only the presence of this condition in our population but also the feasibility and effectiveness of epidural blood patch. It underscores the need for increased awareness and collaboration among clinicians to recognize and manage spontaneous intracranial hypotension patients in Nepal.